Factors influencing the choices of concentration field among liberal studies students in UKM - Fazilah Idris; Wardah Mustafa Din (Penerbit Universiti Kebangsaan Malaysia, 2021)
Universiti Kebangsaan Malaysia is the first public university in Malaysia which takes up the challenge to offer Bachelor of Science in Liberal Studies. This degree is the first personalized curriculum degree which entitles students to choose their own curriculum structure, which is called concentration field in this program. The concentration field is created by students to fulfil their future personal goals and career. This paper will highlight the fields chosen for their concentration and factors contributing to their decision. The study will use self -administered survey to registered Bachelor of Science in Liberal Studies students. The data collected will be analyzed descriptively. Findings show that there are 52 combinations of concentrations fields which cross-disciplines of science, technology, humanities, and social science. Three main factors which influence decision in choosing the concentration field are interest, future career, and academic ability. Two lowest factors are parents and peers influence. This study suggests a model of success for Liberal Studies students includes three internal factors i.e., interest, ambition and academic ability, and three external support which are parents, peers and the university. This paper will give insights to other higher education institutions that are interested in offering this future-focused curriculum in line with the aspiration of the Malaysian Education Blueprint.